Critical role for a promoter discriminator in RpoS control of virulence in Edwardsiella piscicida. - Kaiyu Yin; Yunpeng Guan; Ruiqing Ma; Lifan Wei; Bing Liu; Xiaohong Liu; Xiangshan Zhou; Yue Ma; Yuanxing Zhang; Matthew K Waldor; Qiyao Wang (PLoS Pathogens, 2018)
Edwardsiella piscicida is a leading fish pathogen that causes significant economic loses in the aquaculture industry. The pathogen depends on type III and type VI secretion systems (T3/T6SS) for growth and virulence in fish and the expression of both systems is controlled by the EsrB transcription activator. Here, we performed a Tn-seq-based screen to uncover factors that govern esrB expression. Unexpectedly, we discovered that RpoS antagonizes esrB expression and thereby inhibits production of E. piscicida's T3/T6SS. Using in vitro transcription assays, we showed that RpoS can block RpoD-mediated transcription of esrB. ChIP-seq- and RNA-seq-based profiling, as well as mutational and biochemical analyses revealed that RpoS-repressed promoters contain a -6G in their respective discriminator sequences; moreover, this -6G proved critical for RpoS to inhibit esrB expression. Mutation of the RpoS R99 residue, an amino acid that molecular modeling predicts interacts with -6G in the esrB discriminator, abolished RpoS' capacity for repression. In a turbot model, an rpoS deletion mutant was attenuated early but not late in infection, whereas a mutant expressing RpoSR99A exhibited elevated fitness throughout the infection period. Collectively, these findings deepen our understanding of how RpoS can inhibit gene expression and demonstrate the temporal variation in the requirement for this sigma factor during infection.